I'dadu al-Mu'allim wa Tanmiyatuhu Mihniyyan fi Dhaui al-Ittijahat al-Mu'ashirah - Syakur, Naema al-Mahdi Abu (Al-Wazan: Journal of Arabic Education, 2024)
The landscape of education is continually evolving, shaped by contemporary trends that demand a dynamic and adaptive approach to teacher preparation and professional development. This abstract delves into the critical intersection of "Teacher Preparation and Professional Development in Light of Contemporary Trends." In this exploration, we navigate the transformative shifts in educational paradigms and analyze the consequential impact on how teachers are equipped for the challenges of modern classrooms. By shedding light on the symbiotic relationship between teacher preparation, professional development, and contemporary trends, this abstract contributes to the discourse on enhancing educational practices. It underscores the imperative for educational institutions and policymakers to adopt forward-thinking approaches that align with the evolving needs of both educators and learners in today's ever-changing educational milieu.